Numerical Simulation for Thermal Shock Resistance of Ultra-High Temperature Ceramics Considering the Effects of Initial Stress Field - Weiguo Li; Tianbao Cheng; Dingyu Li; Daining Fang (Advances in Materials Science and Engineering)
Taking the hafnium diboride ceramic as an example, the effects of heating rate, cooling rate, thermal shock initial temperature, and external constraint on the thermal shock resistance (TSR) of ultra-high temperature ceramics (UHTCs) were studied through numerical simulation in this paper. The results show that the external constraint has an approximately linear influence on the critical rupture temperature difference of UHTCs. The external constraint prepares a compressive stress field in the structure because of the predefined temperature field, and this compressive stress field relieves the tension stress in the structure when it is cooled down and then it improves the TSR of UHTCs. As the thermal shock initial temperature, a danger heating rate (or cooling rate) exists where the critical temperature difference is the lowest.